Towards a new approach to the theory of administrative responsibility for governance - Patrón Bedoya, Pedro (2018)
This article develops an innovative perspective related to the administrative responsibility for governance and citing Haldenwang C., the concept of Governance points out: "The concept of Governance is a basic idea shared by most international organizations. This approach covers the presence of democratic and legitimate political institutions, a public administration, efficient and responsible, the rule of law, respect for fundamental rights and effective public regulation of markets ". The author points out that this term has surpassed the concepts of Government and Governance and despite its study, for our reality, it is in relation to Governance and the new approach applicable to the theory of responsibility.